[Dalmacija 1708. - 1918.]. [Druga austrijska uprava u Dalmaciji 1838. - 1847.] : [Objave i oglasi] - Strmić, Antun; Jakšić, Nikola, književnik; Menis, Wilhelm; Turszky, Ivan August; Rossi Sabatini, Giuseppe; Vitezich, Giovanni; Getaldić, Vlaho; Schaller, Ferdinand ([s. n.], 1838)
Objave i oglasi za vrijeme austrijske uprave Dalmacijom 1838. - 1847.